2013
DOI: 10.1007/s11467-013-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor nanowires for photovoltaic and photoelectrochemical energy conversion

Abstract: Semiconductor nanowires (NW) possess several beneficial properties for efficient conversion of solar energy into electricity and chemical energy. Due to their efficient absorption of light, short distances for minority carriers to travel, high surface-to-volume ratios, and the availability of scalable synthesis methods, they provide a pathway to address the low cost-to-power requirements for wide-scale adaptation of solar energy conversion technologies. Here we highlight recent progress in our group towards im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…[77][78][79][80][81][82][83][84][85][86][87] Apart from traditional metal or metal oxide nanowires, semiconductor nanowires have also attracted considerable attention due to their unique properties, such as for lasers, lightemitting diodes, wave guides, logic gates, and devices for energy conversion. [48,[88][89][90][91][92][93] Wu et al reported a successful synthesis of Se nanowires with a length of 10-100 µm and a diameter of about 500 nm and were easily assembled to a Langmuir-Blodgett (LB) film (Figure 3a). [48] Zhang et al [37] reported that Se nanowires with diameters ranging from 20 to 60 nm, were successfully fabricated by a practical and straightforward carbothermal chemical vapor deposition (CVD) route ( Figure 3b).…”
Section: D Se Nanowiresmentioning
confidence: 99%
“…[77][78][79][80][81][82][83][84][85][86][87] Apart from traditional metal or metal oxide nanowires, semiconductor nanowires have also attracted considerable attention due to their unique properties, such as for lasers, lightemitting diodes, wave guides, logic gates, and devices for energy conversion. [48,[88][89][90][91][92][93] Wu et al reported a successful synthesis of Se nanowires with a length of 10-100 µm and a diameter of about 500 nm and were easily assembled to a Langmuir-Blodgett (LB) film (Figure 3a). [48] Zhang et al [37] reported that Se nanowires with diameters ranging from 20 to 60 nm, were successfully fabricated by a practical and straightforward carbothermal chemical vapor deposition (CVD) route ( Figure 3b).…”
Section: D Se Nanowiresmentioning
confidence: 99%
“…They also process a novel superhydrophobic surface preparation method to fabricate micro/nano structures on an Al mold with intensive conical holes by nanosecond laser drilling and HCl etching for droplet pancake bouncing [10]. Under the assistance of air film between water and hydrophobic solid surface, these structures can reduce the contact area between solid and liquid with obviously reducing the friction drag [11][12][13][14][15]. Therefore, achieving the favorable performance of the superhydrophobic surface has attracted more attentions of researchers while researches about drag reduction were still an urgent need in various fields [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the photoelectrolysis cell could automatically separate the hydrogen evolution sites from that of oxygen and enable the photoelectrochemical investigation of materials more easily. The major component of the photoelectrolysis cell, or the photoelectrochemical (PEC) cell, is the photoanode, photocathode or both, and there are many previous reviews for the photoanode and the overall solar water splitting cell [16][17][18][19][20][21][22][23][24][25] . In this feature article, we will focus on providing an overview on the recent efforts in developing photocathodes for solar hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%